Numerical simulation of parameter change in a proton exchange membrane electrolysis cell based on a dynamic model - Chen, Zhichao; Yin, Likun; Wang, Zhiming; Wang, Kaichen; Ye, Feng; Xu, Chao (International journal of energy research, 2022)
Summary In the present paper, a 3‐D, non‐isothermal, two‐phase, transient model was built, and the dynamic characteristics of current density, liquid water saturation, and temperature can be observed after the abrupt changes of voltage, flow rate, and flow direction. The result shows that the changes of temperature with the abrupt change of voltage and flow rate are caused by the change of input electrical energy and the ability of taking heat away, respectively. The time required for temperature stabilization is much longer than the time required for mass transport to achieve relative stable state. For example, the time to reach stability for liquid water saturation and temperature is 1 and 5 s, respectively, when the voltage drops from 2.0 to 1.6 V. The effect of multiple parameters on the high exchange heat capability and temperature difference, which can promote the stabilization process of the internal temperature, should be considered. A higher voltage rise not only causes a temperature rise but also can make the proton exchange membrane electrolysis cell (PEMEC) reach steady state rapidly, resulting in overheat and unsafe operation. The operation strategy changing the water supply mode periodically can be a method that can both control the temperature distribution effectively and improve the PEMEC performance. Based on dynamic model, the dynamic response characteristics of proton exchange membrane electrolysis cell with the abrupt changes of operation parameters are analyzed.